2011
DOI: 10.15228/2011.v01.i03.p03
|View full text |Cite
|
Sign up to set email alerts
|

Serum Malondialdehyde and Lipid Profile Levels of Young Patients "Haven’t a Family History of Hypertension": A New Study for Cases in the Civic Society

Abstract: This study was designed to evaluate the effect of the oxidative stress in sera of young patients without a family history of hypertension, then find the relation of it to lipid profile. The study involved 56 young healthy (30.5 ± 4.7 years) and 23 healthy elderly volunteers (66.3 ± 3.5 years), these individuals were compared with 67 patients (28.6 ± 5.0 years), attending the Gastro Intestinal and Liver Centre at Al Sader Medical City and several specialized clinics in Najaf government. Malondialdehyde level wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…(3,9) In this study a nonsignificant association was found between AI and MDA. Similar results were found in the study of Jasim, (14) but different from the results of the study of yang diperoleh Amirkhizi et al, (15) Linna M et al…”
Section: Discussionsupporting
confidence: 70%
“…(3,9) In this study a nonsignificant association was found between AI and MDA. Similar results were found in the study of Jasim, (14) but different from the results of the study of yang diperoleh Amirkhizi et al, (15) Linna M et al…”
Section: Discussionsupporting
confidence: 70%